TRANSFER FROM GUARDIAN TO JUDICIAL GUARDIAN DURING MARRIAGE IMPLEMENTATION - Teuku Daudsyah (Jurnal Ilmiah METADATA, 2026)
The judge's guardian cannot act as a marriage guardian if the entire group of guardians is still there and their place of residence is known, except in the case of a guardian. The transfer of the nasab guardian to the judge's guardian in a marriage is regulated in the Marriage Law and the Compilation of Islamic Law, which is the implementation of the marriage using the nasab guardian, however, in the implementation of the marriage using the judge's guardian, there must be a certificate obtained from the village where the bride lives. which states that the bride and groom truly fulfill the requirements using the judge's guardian's reasoning, after which the files are put together in a folder. After the administrative requirements have been completed, the implementation process can begin.